PENGARUH KONSERVATISME DAN KARAKTERISTIK PERUSAHAAN TERHADAP PENGHINDARAN PAJAK (TAX AVOIDANCE) (Studi Empiris Pada Perusahaan Pertambangan Yang Terdaftar Di Bursa Efek Indonesia Tahun 2018-2020) - Yusi Lendria Sari; Nofrianty; Zulkarnain (Program Studi Akuntansi Universitas Pasir Pengaraian, 2021)
The purpose of this study was to determine the effect of conservatism and company characteristics on tax avoidance in mining companies listed on the Indonesia Stock Exchange in 2018-2020. This study uses secondary data obtained from the annual reports of mining companies listed on the Indonesia Stock Exchange in 2018-2020. The method used is a quantitative method. The population in this study amounted to 52 companies and obtained a sample of 16 companies with a total of 48 research data. The technique in determining the sample using purposive sampling. The dependent variable in this study is tax avoidance (Y) and the independent variable is conservatism (X1) and company characteristics consisting of profitability (X2), leverage (X3), size (X4), capital intensity (X5) and inventory. intensity (X6) The analytical method used is the method of multiple linear regression analysis. The results of this study indicate that simultaneously conservatism, profitability, leverage, size, capital intensity, and inventory intensity affect tax avoidance (tax avoidance), while partially profitability affects tax avoidance (tax avoidance) and conservatism, leverage, size, capital intensity, and inventory intensity have no effect on tax avoidance.